Manipulasi ikatan Cina bagi hiasan dalaman - Hew, Huai Li (Universiti Malaysia Sarawak (UNIMAS), 2006)
This research focuses on analyzing Chinese knot technique to prevent this handicraft from being forgotten. From the research that was carried out, it is found that product in the market are normally of the same knot, pan chang knot. Besides that, the materials used are of the same, which is silk. In addition, products in the market are limited, especially as wall and car decoration.